Green Purchase Intention Pada Konsumen Nutrifood di Bandung: Peran Environment Concern Dengan Mediasi Green Trust - Dandy Marcelino (Akademi Sekretari Manajemen Taruna Bakti, 2020)
In recent years, global warming has been the subject of controversy and has also changed the rhythm of conservation on Earth. Based on this phenomenon, it will have an impact on the increasing number of companies in Indonesia that carry